2019
DOI: 10.1111/ijfs.14290
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and nutritional characteristics of puffed quinoa

Abstract: Puffed quinoa can be used as ready-to-eat breakfast food or as an ingredient in snack formulations. In this study, puffed quinoa products with and without starch-chitosan coating were developed by gun, extrusion and microwave puffing at different process conditions (pressure, power, moisture content and energy consumption). Size, bulk density, colour, expansion index, water absorption and solubility, microstructure, mechanical and thermal properties, chemical composition and in vitro digestibility of organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 32 publications
4
34
0
Order By: Relevance
“…At the same time, the repose angle showed the following descending order 70.44°> 67.55°> 56.62° for the samples QPI, QPI‐HD, and QPI‐FL, respectively, indicating that the latter sample had a lower angle of internal friction and therefore greater fluidity, which may be related with a smaller particle size (Zhou, Xu, Yu, & Zulli, ). These results are consistent with those reported for puffed quinoa undergoing extrusion and microwaves in which it was found that its microstructure and its mechanical and functional properties were affected (Zapana et al, ).…”
Section: Resultssupporting
confidence: 92%
“…At the same time, the repose angle showed the following descending order 70.44°> 67.55°> 56.62° for the samples QPI, QPI‐HD, and QPI‐FL, respectively, indicating that the latter sample had a lower angle of internal friction and therefore greater fluidity, which may be related with a smaller particle size (Zhou, Xu, Yu, & Zulli, ). These results are consistent with those reported for puffed quinoa undergoing extrusion and microwaves in which it was found that its microstructure and its mechanical and functional properties were affected (Zapana et al, ).…”
Section: Resultssupporting
confidence: 92%
“…EI is one of the major parameters and was used to evaluate the puffing degree of grain after microwave heating (Zapana et al., 2020). The effects of different microwave power treatment on EI of FER are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave heating involves an electromagnetic field focusing on the center of the sample, which may lead to local charring Mom et al (2020). andZapana et al (2020), respectively, observed the same trend in microwaved rice snack and puffed quinoa.…”
mentioning
confidence: 83%
See 2 more Smart Citations